2003
DOI: 10.1002/ps.788
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of pyridalyl: a novel insecticidal agent for controlling lepidopterous pests

Abstract: Synthesis of analogues of two compounds with known insecticidal activity, both of which contain a 3,3-dichloro-2-propenyloxy group, produced 2-(trifluoromethyl)-4-phenoxyphenyl 3,3-dichloro-2-propenyl ether, which had weak activity against lepidopterous larvae. Structural modifications around this lead compound led to the development of pyridalyl [Pleo, S-1812; 2,6-dichloro-4-(3,3-dichloroallyloxy)phenyl 3-[5-(trifluoromethyl)-2-pyridyloxy]propyl ether], which belongs to a new class of insecticides. Pyridalyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 6 publications
1
49
0
Order By: Relevance
“…1), which is highly active against lepidopterous larvae. [1][2][3][4] In a previous study, we observed that Spodoptera litura larvae treated with lethal dosages of pyridalyl lost their vigor, mobile activity and body elasticity, dying within several hours of treatment. In contrast, the topical application of pyridalyl at sub-lethal dosages induced a unique symptom similar to a burn scar at the treated site.…”
Section: Introductionmentioning
confidence: 99%
“…1), which is highly active against lepidopterous larvae. [1][2][3][4] In a previous study, we observed that Spodoptera litura larvae treated with lethal dosages of pyridalyl lost their vigor, mobile activity and body elasticity, dying within several hours of treatment. In contrast, the topical application of pyridalyl at sub-lethal dosages induced a unique symptom similar to a burn scar at the treated site.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridalyl (Figure 1), a novel dichloro-allyloxy-phenol insecticide, was discovered by Sumitomo Chemical Co., Ltd. and marketed in 2004 [12]. It displays good insecticidal activity against different lepidopterous pests on various crops such as cotton and vegetables, and exhibits no cross-resistance with other existing insecticides including synthetic pyrethroids, organic phosphates, benzoylureas and nicotinic insecticides [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is also effective on pests that have developed a resistance to existing insecticides, indicating a different mode of action from any other conventional insecticide [5,6].…”
Section: Introductionmentioning
confidence: 99%